KESADARAN ATAS REALITAS: KAJIAN SVAMI CHINMAYANANDA TERHADAP MANDUKYA UPANISAD - Faisal Yan Aulia (Jurnal Filsafat "WISDOM", 2008)
AbstractKnowledge and technology development has given a lot ofadvantages in the human life. In the other side, bad effects of this development also cause ignorance of spiritual life. The life has only meaning in material relation (in the extensive meaning); between material life and spiritual life, there is unbalanced. For some people, this make an emptiness in their life; their life feels tasteless and has no meaning. Finally, they return to religion to look for answers of question about the meaning of life. Svami Chinmayananda, in his study of Mandukya Upanishad, tries to answer the question by explaining the nature of reality. In this study, he reveals the nature of reality by epistemology and metaphysics perspective. The purpose of this research is giving description about consciousness concept, the nature or reality and consciousness (involves knowledge) which can bring someone to understand the reality which found in Svami Chinmayananda’s study of Mandukya Upanishad. Besides that, the researcher also did critical evaluation about epistemology and metaphysics problems which found in this study.The consciousness of the nature of reality can be a basic guide in living the life and answer problems of the meaning of life.The life which is growing more materialistic needs a balancebetween material world and spiritual world. By discriminativeknowledge (Viveka), someone will reach Turiya consciousness. This Turiya consciousness will bring someone to understand the nature of reality (Atman or Brahman); finally, he/she will understand the meaning of life. Other perspective which is offered by Svami Chinmayananda in his study of Mandukya Upanishad can function as a consideration in living this life.Keywords: Turiya, Avidya, consciousness, reality.